NF-κB-Inducing Kinase Is Essential for Effective c-Rel Transactivation and Binding to the Il12b Promoter in Macrophages - Natalia Cuesta; Anna D. Staniszewska; Cristóbal Moreno; Carmen Punzón; Manuel Fresno (Biology)
This study investigates the role of NIK in activating specific inflammatory genes in macrophages, focusing on the effect of a mutation in NIK found in alymphoplasia (aly/aly) mice. Mouse peritoneal macrophages from aly/aly mice showed a severe defect in the production of some pro-inflammatory cytokines, such as IL-12. This effect seemed to take place at the transcriptional level, as shown by the reduced transcription of Il12b and Il12a in aly/aly macrophages after exposure to the TLR4 agonist LPS. Immunoprecipitation studies showed that the binding of NIK to c-Rel was not efficient in RAW 264.7 cells over-expressing the aly/aly mutation. In addition, the shuttling of c-Rel to the nucleus was shown to be impaired in aly/aly macrophages in response to LPS. When looking more specifically at the regulation of the Il12b promoter, we found that c-Rel bound to the NF-kB consensus sequence in macrophages from WT mice 1 hr. after LPS challenge, whereas in aly/aly macrophages, the transcription factor bound to the promoter was p65. These findings indicate that NIK is essential for efficient c-Rel activation and proper inflammatory responses. NIK dysfunction could lead to weakened immune responses, and targeting this pathway may help in developing therapies for immune-related conditions.